Rancang Bangun Website Desa Demangharjo - Destiana Putri; Windu Gata; Warjiyono (STEKOM PRESS, 2020)
The internet as a communicator of information is now a necessity. Particularly in the provision of information for a company, government organizations / agencies such as Village Centers that require a fast, precise and accurate data management system that can provide more complete, up-to-date, interactive and dynamic information. In Demangharjo Village the information system related to Village Information is still submitted in the form of a guide book and the service is still done manually. Basically, population residence service activities are required to take care of application letters at the village office with the applicable procedures, so that in practice it will certainly take a long time and energy. For this reason the author made the Final Project concerning the Design of Demangharjo Village Website with the metedo Waterfall. Through this website, it is expected that information will be conveyed more quickly and accurately, maximum service and information transparency, village introduction process and population data storage to accelerate the work of village officials in serving the community and make it easier for citizens to submit services or find out village information.